Odpowiedzi

2010-02-01T16:32:02+01:00
A)
x=5 => 7
x=2 => 1
x=0 => -3
x=-1 => -5
x=-3 => -9
b)
x=10 => -55
x=1 => 1
x=0,1 => 5,5
x=0 => 6
x=-0,2 => 7
c)
x=0,25 => 4
x=0,125 =>3
x=0,1 => 2,8
x=-0,2 => 0,4
x = -2,5 =>-18
2010-02-01T16:52:15+01:00
A) 2x-3=
* x=5
2*5-3=7

2x-3=
x=2
2*2-3 = 1
2x-3 =
x=0
2*0 -3 = 0

2x-3 =
x= -1
2 * (-1) - 3= -5
2x-3 =
x= -3
2*(-3) -3 = -9
b)
6- 5x
x=10
6- 5*10 = -44
6- 5x
x=1
6- 5*1 =1
6-5x
x= 0,1
6 -5*0,1=5,5

6-5x=
x=0
6-5*0 =
6-0 =6

6-5x=
x= 0,2
6- 5* (-0,2)=
6-(-1)= 7

c) 8x+2
x= 0,5
8* 0,5 +2
4+2=6

8x+2
x= 0,25
8*0,25 +2
2+2=4

8x+2
x= 0,125
8* 0,125+2
1+2 =3

8x+2
x= 0,1
8* 0,1+ 2
0,8+2= 2,8
8x+2
x=- 0,2
8* (-0,2) +2
-1,6 +2= 0,4

8x+2
x= - 2,5
8* (-2,5)+2
-20+2=18
1 5 1